Bottom Copy Pronunciation in Japanese Passives - Abe, Jun (Studia linguistica, 2024)
On the basis of Abe's (2016) proposal that in the case of an A‐chain, any member can be the target for pronunciation, I argue that Japanese passives may have the bottom copies of the produced A‐chains pronounced. When the passivized subjects appear to occupy their original θ‐positions, it is standardly claimed that the relevant word order is derived by scrambling other material sentence‐initially. Contrary to this claim, I demonstrate that there are cases, including those of what Miyagawa (1989) calls the causative‐passive construction, where the passivized subjects actually occupy their original θ‐positions. I then provide evidence that those passivized subjects undergo “covert” A‐movement, hence giving support to my bottom copy pronunciation analysis.